Building Plans of St. Alexander Nevsky Orthodox Church in Łódź – Analysis of Documentation - Śródkowska, Agata (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
The aim of the article is to present architectural documentation of the Orthodox church. St. Alexander Nevsky in Lodz. The building was built in the 1880s. These plans have been used as illustrative material, including in the work of Krzysztof Stefański titled “The sacred architecture of Łódź during the industrial development of the city of 1821–1914”. However, they have not been described in detail. Currently, they are stored in the collection of the Provincial Office for the Protection of Monuments in Lodz. The author draws attention to the external features of the project, material and technique, but also to the performance time and content in the text. An auxiliary material was also issued in the 1860s in the “Collection of Administrative Provisions of the Kingdom of Poland” building regulations, in which guidelines regarding the preparation of this type of documentation were included. By the way, the author checks whether the plans for the construction of the church were made by the architect in accordance with the then applicable legal regulations. The article is supplemented with photographs showing individual parts of the project and the church itself in its present state.